Transcriptomic analysis displays the effect of (-)-roemerine on the motility and nutrient uptake in Escherichia coli - Ayyildiz, Dilara; Wozny, Katharina; Brügger, Britta (Current genetics, 2017)
Among the different families of plant alkaloids, (-)-roemerine, an aporphine type, was recently shown to possess significant antibacterial activity in Escherichia coli. Based on the increasing demand for antibacterials with novel mechanisms of action, the present work investigates the potential of the plant-derived alkaloid (-)-roemerine as an antibacterial in E. coli cells using microarray technology. Analysis of the genome-wide transcriptional reprogramming in cells after 60 min treatment with 100 μg/mL (-)-roemerine showed significant changes in the expression of 241 genes (p value <0.05 and fold change >2). Expression of selected genes was confirmed by qPCR. Differentially expressed genes were classified into functional categories to map biological processes and molecular pathways involved. Cellular activities with roles in carbohydrate transport and metabolism, energy production and conversion, lipid transport and metabolism, amino acid transport and metabolism, two-component signaling systems, and cell motility (in particular, the flagellar organization and motility) were among metabolic processes altered in the presence of (-)-roemerine. The down-regulation of the outer membrane proteins probably led to a decrease in carbohydrate uptake rate, which in turn results in nutrient limitation. Consequently, energy metabolism is slowed down. Interestingly, the majority of the expressional alterations were found in the flagellar system. This suggested reduction in motility and loss in the ability to form biofilms, thus affecting protection of E. coli against host cell defense mechanisms. In summary, our findings suggest that the antimicrobial action of (-)-roemerine in E. coli is linked to disturbances in motility and nutrient uptake.